2006
DOI: 10.1111/j.1447-0349.2006.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Staff gender ratio and aggression in a forensic psychiatric hospital

Abstract: Gender balance in acute psychiatric inpatient units remains a contentious issue. In terms of maintaining staff and patient safety, 'balance' is often considered by ensuring there are 'sufficient' male nurses present on each shift. In an ongoing programme of research into aggression, the authors investigated reported incidents of patient aggression and examined the gender ratio on each shift over a 6-month period. Contrary to the popular notion that a particular gender ratio might have some relationship with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 37 publications
3
29
1
1
Order By: Relevance
“…8 This accords well with a study by Hatch-Maillette who found that male staff viewed threat situations as significantly less threatening than female staff. 9 In a further study in 2003, the same author highlights similar issues making the link between employee well-being, job satisfaction, morale and organisational productivity.…”
Section: Discussionsupporting
confidence: 87%
“…8 This accords well with a study by Hatch-Maillette who found that male staff viewed threat situations as significantly less threatening than female staff. 9 In a further study in 2003, the same author highlights similar issues making the link between employee well-being, job satisfaction, morale and organisational productivity.…”
Section: Discussionsupporting
confidence: 87%
“…One aspect is how staff described conflicts between staff members and patients and how this was reflected in discussions about rules and routines. This touches upon and confirms what Daffern, Mayer, and Martin (2006) mention with regard to the physical strength of male staff members, which provides staff with the self-confidence to handle difficult situations. In forensic psychiatric care this is nothing unusual.…”
Section: To Protect and Prevent Violencesupporting
confidence: 84%
“…Daffern, Mayer, and Martin (2006) question this assumption of a sufficient number of male caregivers to prevent situations of violence and threats at the units. Connell (1993Connell ( , 1995Connell ( , 2000Connell ( , 2003 argues that while attitudes and values of men's physical strength can generate higher status for men, they also can create a difference between men's and women's assignments.…”
mentioning
confidence: 99%
“…Carmel and Hunter (1989) also suggested that male staff may attempt to contain physically patients' aggressive behaviour more than female staff, thus exacerbating aggressive behaviour from the patients towards them. Daffern, Mayer, and Martin (2006) found that staff tended to be more confident in managing aggressive incidents when more male staff were present on shift. However, they found no statistical link between the number of aggressive incidents and the staff sex mix on the ward at the time.…”
mentioning
confidence: 95%